"SINGING THE HEALING": THE RITUALS OF THE TWELVE APOSTLES CHURCH IN GHANA - Asare, Amos Darkwa (International Library of African Music, 2019)
While many in Ghana prefer modern medical systems, others use indigenous means such as those emanating from shrines and indigenous sects. Today, many religious practices in Ghana focus a greater part of their services on healing and the general wellbeing of its members. The formation of African Indigenous Churches (AICs) has played a central role in bridging the gap between indigenous and Christian concepts of worship, healing, and wellbeing. The Twelve Apostles Church, first of the AICs in Ghana, is prominent as far as good health and the wellbeing of its members are concerned. These indigenous musical healing practices are seldom recognised for their significant contribution towards good health and wellbeing. In this article, I use an ethnographic approach, employing interviews and participant observation, to describe the significance of the musical healing rituals of the Twelve Apostles Church in Ghana. The question is, how does drumming, dancing, and singing in the Twelve Apostles Church contribute to good health and wellbeing?
Keywords: Worship; Healing; Religion; Ritual; Well-being; African Indigenous Churches; Indigenous Music; African Music; Ghana